IMPACT EVALUATION OF THE STABILITY OF THE PRODUCTION TO ENSURE THE PRODUCT QUALITY - Kupryian, Yu. A. (Science and Transport Progress, 2006)
In the article considered dependence of accordance of products to the requirements of normative documents on its making from the correct choice and estimation of key descriptions of products, and similarly technological process of its making.